The impact of humidity on building materials in heritage residential buildings-Sulaimani city as a case study - Salih, Chro A. H.; Seed, Bahar H. (Sulaimani Journal for Engineering Sciences, 2019)
Building materials are important factors that have given heritage buildings special feature and distinct it from other modern buildings. These materials are usually taken from the sources that were available in that region, such as wood, clay, plaster, stone ... etc., as they have been affected by various factors such as humidity. Humidity is one of the basic components of a natural environment that affects buildings in general and the residential buildings in particular. Humidity causes rot, melting, collapse, corrosion and bending in building materials, and this can be seen in selected models in the heritage areas of Sulaimani city. The research assumes that humidity affects building materials in varying degrees. Then through graphic analysing and also analysing the table of indicators, the hypothesis of the research has been tested and the main conclusions have been discussed.
Keywords: Residential buildings; heritage; Building materials; climatic factors; humidity